Effectiveness of Multicomponent Interventions in Office-Based Workers to Mitigate Occupational Sedentary Behavior: Systematic Review and Meta-Analysis - Liying Zhou; Xinxin Deng; Kangle Guo; Liangying Hou; Xu Hui; Yanan Wu; Meng Xu; Yongsheng Wang; Shanshan Liang; Kehu Yang; Xiuxia Li (JMIR Publications, 2023)
BackgroundSedentary time in workplaces has been linked to increased risks of chronic occupational diseases, obesity, and overall mortality. Currently, there is a burgeoning research interest in the implementation of multicomponent interventions aimed at decreasing sedentary time among office workers, which encompass a comprehensive amalgamation of individual, organizational, and environmental strategies. ObjectiveThis meta-analysis aims at evaluating the effectiveness of multicomponent interventions to mitigate occupational sedentary behavior at work compared with no intervention. MethodsPubMed, Web of Science, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) databases were searched from database inception until March 2023 to obtain randomized controlled trials (RCTs) assessing the efficacy of multicomponent interventions on occupational sedentary behavior among office-based workers. Two reviewers independently extracted the data and assessed the risk of bias by using the Cochrane Collaboration's risk of bias tool. The average intervention effect on sedentary time was calculated using Stata 15.1. Mean differences (MDs) with 95% CIs were used to calculate the continuous variables. Subgroup analyses were performed to determine whether sit-stand workstation, feedback, and prompt elements played an important role in multicomponent interventions. Further, the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) system was used to evaluate the certainty of evidence. ResultsA total of 11 RCTs involving 1894 patients were included in the analysis. Five studies were rated as low risk of bias, 2 as unclear risk of bias, and 4 as high risk. The meta-analysis results showed that compared with no intervention, multicomponent interventions significantly reduced occupational sitting time (MD=-52.25 min/8-h workday, 95% CI -73.06 to -31.44; P<.001) and occupational prolonged sitting time (MD=-32.63 min/8-h workday, 95% CI -51.93 to -13.33; P=.001) and increased occupational standing time (MD=44.30 min/8-h workday, 95% CI 23.11-65.48; P<.001), whereas no significant differences were found in occupational stepping time (P=.06). The results of subgroup analysis showed that compared with multicomponent interventions without installment of sit-stand workstations, multicomponent interventions with sit-stand workstation installment showed better effects for reducing occupational sitting time (MD=-71.95 min/8-h workday, 95% CI -92.94 to -51.15), increasing occupational standing time (MD=66.56 min/8-h workday, 95% CI 43.45-89.67), and reducing occupational prolonged sitting time (MD=-47.05 min/8-h workday, 95% CI -73.66 to -20.43). The GRADE evidence summary showed that all 4 outcomes were rated as moderate certainty. ConclusionsMulticomponent interventions, particularly those incorporating sit-stand workstations for all participants, are effective at reducing workplace sedentary time. However, given their cost, further research is needed to understand the effectiveness of low-cost/no-cost multicomponent interventions.